An Evaluation of Procedural Training in Canadian Respirology Fellowship Programs: Program Directors’ and Fellows’ Perspectives - David Ryan Stather; Julie Jarand; Gerard A Silvestri; Alain Tremblay (Canadian Respiratory Journal)
BACKGROUND: In recent years, there has been a rapid growth in diagnostic and therapeutic procedures performed by respirologists.